Do foreign ownership and board characteristics matter for carbon emission disclosure in Indonesian banks? - Khairun Nisaa; Doddy Setiawan (Postgraduate Program Merdeka University, 2026)
This study analyzes the impacts of foreign influence on carbon emission disclosure across three dimensions: foreign ownership, foreign directors, and directors’ international experience. A dataset utilized in this study is 325 observations to 43 conventional commercial banks listed on the Indonesia Stock Exchange (IDX) over the period 2017–2024. Employing multiple linear regression with a fixed-effects model (FEM) in Stata 17, the findings reveal that foreign ownership shows no significant effect on CED. Implying the legitimacy pressure from ownership alone, as proposed by Legitimacy Theory, is insufficient without direct board involvement. In contrast, foreign directors and directors’ international experience demonstrates significantly affect CED, supporting Upper Echelons Theory, by which explains this effect through directors' characteristics. These findings suggest that director characteristics is driven more than foreign ownership in affecting carbon emission disclosure, highlighting the role of corporate governance in supporting the achievement of the Sustainable Development Goals (SDGs) in the Indonesian banking sector. This study contributes to the carbon disclosure and corporate governance literature by identifying three dimensions of foreign influence into a single analytical framework, as compared to previous studies that examined these factors separately, thus offering a more comprehensive governance perspective on how the involvement of foreign attributes can shape firms' strategic decisions to enhance carbon emission transparency.